Analysis of the equilibrium strategies in the GeoGeo1 queue with multiple working vacations. Issue 6 (2nd November 2018) - Yang, Bixuan; Hou, Zhenting; Wu, Jinbiao
Abstract : In this paper, we deal with the customers' equilibrium strategies in a Geo  /  Geo  / 1 queuing system with multiple working vacations. The arriving customers decide whether to join or balk the queuing system depended on the information of the server's states and the queue length. Based on the reward-cost structure, we obtain the equilibrium balking strategies and socially optimal strategies in three cases of the fully observable queue, the partially observable queue and the unobservable queue. In addition, we provide some numerical experiments to illustrate the influence of the information level on the equilibrium behavior and to compare the customers' equilibrium and socially optimal strategies.